Recognising contributions to work in research collaboratives: Guidelines for standardising reporting of authorship in collaborative research. (April 2018) - ,; Blencowe, Natalie; Glasbey, James; Heywood, Nick; Kasivisvanathan, Veeru; Lee, Matthew; Nepogodiev, Dmitri; Wilkin, Richard; Allen, Sophie; Borakati, Aditya; Bosanquet, David; Chapman, Stephen; et al.
Abstract: Background: Trainee research collaboratives (TRCs) have been revolutionary changes to the delivery of high-quality, multicentre research. The aim of this study was to define common roles in the conduct of collaborative research, and map these to academic competencies as set out by General Medical Council (GMC) in the United Kingdom. This will support trainers and assessors when judging academic achievements of those involved in TRC projects, and supports trainees by providing guidance on how to fulfil their role in these studies. Methods: A modified Delphi process was followed. Electronic discussion with key stakeholders was undertaken to identify and describe common roles. These were refined and mapped to GMC educational domains and International Committee of Medical Journal Editors authorship (ICJME) guidelines. The resulting roles and descriptions were presented to a face-to-face consensus meeting for voting. The agreed roles were then presented back to the electronic discussion group for approval. Results: Electronic discussion generated six common roles. All of these were agreed in face-to-face meetings, where two further roles identified and described. All eight roles required skills that map to part of the academic requirements for surgical training in the UK. Discussion: This paper presents a standardised framework for reporting authorship in collaborative group authored research publications. Linkage of collaborator roles to the ICMJE guidelines and GMC academic competency guidelines will facilitate incorporation into relevant training curricular and journal publication policies.